Traditional and Alternative Therapies for Refractory Angina - Kocyigit, Duygu; Murat Gurses, Kadri; Ulvi Yalcin, Muhammed; Tokgozoglu, Lale (Current Pharmaceutical Design, 2017)
Refractory angina (RFA) is an unfavourable condition that is characterized with persistent angina due to reversible myocardial ischemia in patients with coronary artery disease that remains uncontrollable despite an optimal combination of pharmacological agents and revascularization. Despite significant advances in revascularization techniques and agents used in pharmacological therapy, there is still a significant population suffering from RFA and the global prevalence is even increasing. Anti- anginal treatment and secondary risk-factor modification are the traditional approaches for this group of patients. Furthermore, now there is still a large number of alternative treatment options. In order to review traditional and alternative treatment strategies in patients with RFA, we searched Pubmed for articles in English using the search terms “pharmacological therapy, refractory angina”, “alternative therapy, refractory angina” between inception to June 2016. We also went through separately for each alternative treatment modality on Pubmed. To identify further articles, we handsearched related citations in review articles and commentaries. We also included data from the European Society of Cardiology (2013), and the Canadian Society of Cardiology/ Canadian Pain Society (2012) guidelines. Data show that besides traditional pharmacological agents, such as nitrates, beta- blockers or calcium channel blockers, novel antiischemic drugs and if symptoms persist, several non- invasive and/ or invasive alternative strategies may be considered. Impact of some pharmacological agents, such as rho- kinase inhibitors, and novel alternative treatment modalities, such as coronary sinus reducers, stem cell therapy, gene and protein therapy, on outcomes are still under investigation.
Keywords: alternative